2022
DOI: 10.1038/s41467-022-32001-z
|View full text |Cite
|
Sign up to set email alerts
|

Warming and redistribution of nitrogen inputs drive an increase in terrestrial nitrous oxide emission factor

Abstract: Anthropogenic nitrogen inputs cause major negative environmental impacts, including emissions of the important greenhouse gas N2O. Despite their importance, shifts in terrestrial N loss pathways driven by global change are highly uncertain. Here we present a coupled soil-atmosphere isotope model (IsoTONE) to quantify terrestrial N losses and N2O emission factors from 1850-2020. We find that N inputs from atmospheric deposition caused 51% of anthropogenic N2O emissions from soils in 2020. The mean effective glo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 119 publications
1
27
0
Order By: Relevance
“…Since the inversion model estimates EFs based on observed changes in atmospheric N 2 O concentrations, it accounts for both direct and indirect emissions. Indirect emissions were not included in our study but account for about one‐third of total cropland N 2 O emissions (Harris et al., 2022). Comparing our findings with the IPCC Tier 1 defaults, significant increases in EFs were found in Russia, Myanmar and some areas dominated by acidic soils and single cropping systems (e.g., wheat and maize) (Figure 4b), while the increase was trivial in East India and Pakistan, probably due to the vast expansion of double cropping systems (e.g., rice‐upland crops and upland‐upland crops) with shorter fallow durations (Sacks et al., 2010; Waha et al., 2020), alongside the prevalence of alkaline soils in Pakistan.…”
Section: Resultsmentioning
confidence: 99%
“…Since the inversion model estimates EFs based on observed changes in atmospheric N 2 O concentrations, it accounts for both direct and indirect emissions. Indirect emissions were not included in our study but account for about one‐third of total cropland N 2 O emissions (Harris et al., 2022). Comparing our findings with the IPCC Tier 1 defaults, significant increases in EFs were found in Russia, Myanmar and some areas dominated by acidic soils and single cropping systems (e.g., wheat and maize) (Figure 4b), while the increase was trivial in East India and Pakistan, probably due to the vast expansion of double cropping systems (e.g., rice‐upland crops and upland‐upland crops) with shorter fallow durations (Sacks et al., 2010; Waha et al., 2020), alongside the prevalence of alkaline soils in Pakistan.…”
Section: Resultsmentioning
confidence: 99%
“…Warming and acidification are crucial factors affecting N 2 O emissions, , and a profound understanding of associated mechanisms regarding N 2 O production and reduction is of great significance to project the sources and sinks of N 2 O in aquatic ecosystems. Previous studies have reported that bacteria and fungi show different resilience to warming and acidification, ,, thereby leading to different N 2 O production.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the isotope data of N 2 O from 1940 to 2020 obtained by Harris et al. (2022), integrating this isotope data with the process model emerges as a promising direction for future. Consequently, quantification of denitrification N losses is crucial not only for understanding variation in soil N retention within soil but also for addressing a notable scientific challenge in N cycling.…”
Section: Limitations and Future Workmentioning
confidence: 99%